'Malik Ambar ki Pipeline': Reconstructing the Past Through Community Memories. (November 2020) - Mubayi, Yaaminey
Situated in the arid heart of the Deccan, Daulatabad has been the centre of historic settlements dating back to the first millenniumad . Its geo-political significance lies in its location along sub-continental trade and pilgrimage routes, causing it to be named 'Khadki' or window to the south, a strategic position that prompted Mohammed bin Tughlaq to shift his capital from Delhi to Daulatabad. However, the reason for the continued relevance of Daulatabad as an important settlement is the paradoxical ability of human communities to access and manage water in an arid and inhospitable environment. From the water cisterns of the nearby Ellora caves to wells, baolis, tanks and talaabs, natural and man-made, the landscape burgeons with evidence of the human ability to salvage every drop of water, both underground and overground. Nowhere is this skill more ably demonstrated than in the hydrological works of Malik Ambar, an Abyssinian slave who rose to become the de facto ruler of the Nizamshahi dynasty in the sixteenth to seventeenth centuries and is still recognised as a hero by the local community today. Much has been written about this remarkable personality, his origins in the Kambata region of Ethiopia, his travel to the sub-continent via the Arab slave trade, his rise to become the Vakil us Saltanat of the Nizam Shahis of Ahmadnagar and his legendary defence of the kingdom against Mughal expansion into the Deccan. This article, however, explores a less-known aspect of Ambar's career, his role in constructing an extraordinary system of water management that enhanced the capacities of Daulatabad fort to enable it to support a large garrison and indeed, become a second capital of the Nizamshahi sultanate. Through site-based interactions and conversations with the local community, the personality of Malik Ambar as a local hero and his influence in the region has been reconstructed, enabling an interesting perspective of a historic personage 'from below'.